Nitrogen and sulfur mineralization in Brazilian soils under influence of liming and phosphorus - Silva, Carlos Alberto; Vale, Fabiano Ribeiro do; Anderson, Sharon Jill; Kobal, Alex Rodrigues (Pesquisa Agropecuaria Brasileira, 1999)
This study was carried out under laboratory conditions, from October 1995 to January 1996, in order to evaluate the influence of liming and phosphorus (P) application on nitrogen (N) and sulfur (S) mineralization in seven Brazilian (0-20 cm) soils with a wide variability in chemical and physical properties. Soil samples, before fertilization with P (KH2PO4), were pre-incubated during seven days with CaCO3, and incubated again for another 70 days. The content of mineralized N (NH4+ and NO3-) and S (SO42-) were measured every other week, in aerobic conditions. Transformation of N and S showed different mineralization patterns from each other, with mineral N levels undergoing much greater variation than sulfate levels. Mineralized N amounts were not affected by soil acidity, although liming accelerated N mineralization in Humic Gley and Red-Yellow Latosol (colected in Rio de Janeiro) soils. Liming the soils to a pH around 6.0 resulted in increased net S mineralization in Low Humic Gley and Red-Yellow Latosol (colected in Rio de Janeiro) soils. Addition of superphosphate did not influence N and S mineralization processes. The greater prevalence of nitrate and sulphate in some of the limed soils suggests that the criterion used to choose time of lime application needs to be changed.